Analisis Kesulitan Siswa Kelas 4 SD Negeri 106162 Medan Estate dalam Memahami Pola Bilangan dan Solusi Pembelajarannya - Irawan Saragih, Doni; Siti Aulia, Abel; Putri, Andini; Aisy Sitorus, Rihadatul; Syafitri, Nabila (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Understanding number patterns is an essential aspect of elementary mathematics education. However, many fourth-grade students at SD Negeri 106162 Medan Estate struggle with this concept. This study aims to analyze the types of difficulties students face and explore effective learning solutions. A qualitative descriptive research method was used, with data collection techniques including observation, diagnostic tests, interviews, and documentation. The findings indicate that students' difficulties involve understanding number pattern concepts, applying patterns to contextual problems, and the lack of interactive teaching methods. To overcome these issues, the "Guess the Pattern with Number Cards" game method was implemented. Evaluation results showed significant improvements in students' understanding of number patterns and increased their motivation to learn. This study highlights the importance of innovative and interactive teaching approaches in helping elementary school students grasp mathematical concepts effectively.